IDENTIFIKASI KESULITAN CALON GURU TAMAN KANAK-KANAK DALAM MEMPELAJARI MUSIK - Marwati Mansyur (Perspektif Ilmu Pendidikan, 2007)
The objectives of this research are to discover the difficulties faced by the students as the candidates for kindergarten teachers in studyint music, to identify the kinds of the difficulties, to know the students ‘knowledge of musical instruments, and to measure the degrees of students’ creativity in learning music. The research used survey conducted as from May through November 2005 in The Study Program of PGTK within the Department of Child Education, Schoolof Education, State University of Jakarta. The population covered all students of the Program Study of D-II PGTK which were doing music course. The respondents were choosen by random sampling technique with the total number of 40 students. The result of the study show that (1) background knowledge of music in skill low, (2) reading musical notation is the most difficult to study, (3) the best known musical instrument is tambourine and the best known is castanyet and (4) student’s creativity in learning music is categorized high.